2008
DOI: 10.1037/1524-9220.9.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Peer crowd affiliations of adult gay men: Linkages with health risk behaviors.

Abstract: The social networks of adult gay men play important roles in both the promotion and prevention of health risk. The current investigation had 2 primary goals. First, this study examined the existence of gay peer crowds using the opinions of a large (N ϭ 340) online sample of self-identified gay men. Second, it explored how these peer crowd affiliations may be differentially related to health risk. All participants provided demographic information, opinions regarding the existence of gay peer crowds, and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 38 publications
4
47
0
2
Order By: Relevance
“…Risk factors identified in this review that could be considered unique to sexual minorities include internalised homophobia,46 reactions to disclosure of sexual orientation,87 and identity within sexual minority communities (eg, ‘goth’ identity or presentation of masculinity/femininity) 67 80. Research conducted after the search time for the present review indicates some evidence for smoking risk based on presentation of masculinity or femininity,88 which is compatible with historical scholarship 89.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Risk factors identified in this review that could be considered unique to sexual minorities include internalised homophobia,46 reactions to disclosure of sexual orientation,87 and identity within sexual minority communities (eg, ‘goth’ identity or presentation of masculinity/femininity) 67 80. Research conducted after the search time for the present review indicates some evidence for smoking risk based on presentation of masculinity or femininity,88 which is compatible with historical scholarship 89.…”
Section: Discussionsupporting
confidence: 69%
“…In contradiction with those findings, Willoughby and colleagues did not find an association between smoking and family rejection 73. An array of risks were examined, from religiosity being protective against smoking among heterosexual adolescents but not sexual minority adolescents,79 to bisexual women having greater odds of smoking for weight control than lesbian women,25 to differential associations of smoking among subcultures of sexual minority populations 67 80…”
Section: Resultsmentioning
confidence: 91%
“…For instance, in the general literature on adolescent health, peers play a strong role in the development and maintenance of risk behaviors (La Greca, Prinstein, & Fetter, 2001). Peers also appear to play a critical role in the health risk behaviors (e.g., marijuana use, binge drinking, cigarette smoking) of adult sexual minorities (Willoughby, Lai, Doty, Mackey, & Malik, 2008). In addition, emerging evidence shows that different neurobiological systems are thought to underlie internalizing versus externalizing problem behaviors (Rothbart & Bates, 1998).…”
Section: Internalizing Problems Versus Health Risk Behaviorsmentioning
confidence: 98%
“…For instance, Willoughby, Lai, Doty, Mackey, and Malik (2008) found that, in a sample of gay men, self-identified subgrouping categories (e.g., Goths, Twinks, Bears) differentiated prevalence of current (i.e., once in past 30 days) smoking. Rosario, Schrimshaw, and Hunter (2008) noted that among lesbians, women who identified as butch (i.e., more masculine) tended to smoke more than women who identified as femme (i.e., more feminine).…”
Section: Discussionmentioning
confidence: 99%